Anti-cracking composite base coat for base surface renovation and preparation process of anti-cracking composite base coat
By adding elastic emulsion and newly developed adhesion accelerator to the formula of the base surface refurbishing composite primer, the crack problems caused by temperature changes and concrete shrinkage of the building wall base are solved, efficient crack resistance and bonding strength are achieved, and the service life of the wall is extended.
Patent Information
- Application Number
- CN202411937389.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-26
AI Technical Summary
During long-term use, the base layer of building walls is prone to produce fine turtle-like cracks due to temperature changes and concrete shrinkage, which affects the decorative effect and service life. The existing technology is difficult to effectively solve this problem.
By adding elastic emulsion and newly developed adhesion promoters to the formulation of refurbished composite primer on the base surface, the crack resistance and bond strength of the paint are improved, ensuring that the paint forms a firm adhesion with the substrate.
It has achieved excellent crack resistance of base surface renovation composite primer, and can meet the technical standards of R-type flexible building exterior wall putty in JG/T 157-2009 "Exterior Wall Putty for Buildings", significantly improving the bonding strength and extending the service life of the wall.
Smart Images

Figure BDA0005211827270000051 
Figure BDA0005211827270000052 
Figure BDA0005211827270000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of research and development of architectural coatings, in particular to a crack-resistant base surface renovation composite primer and a preparation process thereof. Background Art
[0002] Base surface renovation refers to the process of reprocessing and repairing the basic surface of a building or ground to improve its appearance, performance or extend its service life. Among them, the composite primer is a key layer of material in the base surface renovation coating system, mainly providing functions such as base treatment and leveling, adhesion to the substrate, product thickness, modeling, crack resistance, waterproofing, and coloring.
[0003] The primer is a liquid substance applied to the substrate before construction. After solidification, it forms a firm coating film that is strongly adsorbed on the surface of the substrate. This adsorption is not only physical adsorption, but also chemical bonding, that is, chemical adsorption. The primer is a transition layer between the base surface and the substrate. Because its bonding strength with the base adhesive and the substrate is better than the bonding strength between the base adhesive and the substrate, it strengthens the bonding performance between the base adhesive and the substrate.
[0004] The building walls are exposed to the atmosphere for a long time. Affected by natural factors such as thermal expansion and contraction, temperature changes, and the shrinkage of concrete hardening, the wall base is prone to small turtle-shaped cracks, which expand with the extension of service time. In mild cases, it will affect the surface decoration effect of the building, and in severe cases, it will even cause water seepage on the wall, seriously affecting the decoration effect and service life of the exterior wall. Therefore, in order to meet the needs of cracking and expansion of the wall base material and covering the fine cracks of the base, it is of certain practical significance to develop a crack-resistant base renovation composite primer.
[0005] At present, the main ways to improve the crack resistance of coatings are: selecting Si-O bond molecular chains with larger bond energy as the main film-forming resin emulsion, overcoming the disadvantage of short UV resistance time of ordinary film-forming resin emulsions containing CC bond molecular chains (such as using silicone film-forming resin emulsions, etc.); adjusting the microscopic network structure of the film-forming resin molecular chain so that the resin has better elasticity and avoids coating cracking caused by temperature gradient impact (such as adding elastic emulsions, etc.); adding an adhesion promoter with high compatibility with the film-forming resin emulsion so that the coating has excellent adhesion to the substrate and avoids cracking of the coating caused by substrate expansion and contraction.
[0006] The present invention refers to the chemical structure and preparation method of octaaminopropyl POSS (OA-POSS) disclosed in the article "Research on DOPO Derivatives / Octaminopropyl POSS Flame-Retardant Wood-Plastic Composite Materials" published by Zhang Ling et al., which was published in the Journal of Southwest Forestry University, Volume 43, Issue 3, Pages 136-144, May 2023. Summary of the invention
[0007] The invention provides a preparation process of a base surface renovation composite primer with anti-cracking properties. On the one hand, an elastic emulsion raw material is added into the formula to achieve the technical goal of improving the anti-cracking performance of the coating. On the other hand, a newly developed adhesion promoter is used to improve the bonding strength between the primer and the substrate, thereby ensuring that the composite primer forms a firm adhesion on the surface of the substrate. The base surface renovation composite primer prepared in this way can meet the technical standard of R-type flexible building exterior wall putty in JG / T 157-2009 "Building Exterior Wall Putty".
[0008] A preparation process of a crack-resistant base surface renovation composite primer comprises the following steps:
[0009] Step 1: preparing an adhesion promoter containing a methoxy functional group, wherein the adhesion promoter containing a methoxy functional group is one of adhesion promoter I, adhesion promoter II, and adhesion promoter III;
[0010] Step 2: preparing a crack-resistant base surface renovation composite primer, the formula of the crack-resistant base surface renovation composite primer is: 15-20 parts by weight of water, 5-15 parts by weight of silicone-modified polyester resin emulsion, 5-15 parts by weight of silicone-acrylic emulsion, 5-15 parts by weight of elastic emulsion, 5-10 parts by weight of cellulose, 0.1-1 parts by weight of antifreeze agent, 0.5-2 parts by weight of film-forming aid, 0.1-1 parts by weight of pH adjuster, 1-3 parts by weight of dispersant, 1-3 parts by weight of defoamer, 0.1-1 parts by weight of wetting agent, 15-30 parts by weight of filler, 1-5 parts by weight of protective glue, 1-3 parts by weight of protective glue auxiliary, 1-3 parts by weight of thickener, 1-3 parts by weight of preservative, 1-3 parts by weight of adhesion promoter and 1-3 parts by weight of cross-linking agent.
[0011] Preferably, the preparation method of the adhesion promoter I is: the alkenyl functional group of allyltrimethoxysilane is reacted with the Si-H functional group of 1-n-butyl-1,1,3,3-tetramethyldisiloxane to generate the adhesion promoter I.
[0012] Preferably, the preparation method of the adhesion promoter II is: under the catalytic action of a phase transfer catalyst, the hydroxyl functional group of 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane and the chlorine functional group of 3-chloropropyltrimethoxysilane undergo a nucleophilic substitution reaction to generate adhesion promoter II.
[0013] Preferably, the phase transfer catalyst is one of benzyltriethylammonium chloride, tetrabutylammonium hydrogen sulfate and tetrabutylammonium bromide.
[0014] Preferably, the preparation method of the adhesion promoter III is: a nucleophilic substitution reaction occurs between the bromine functional group of 3-chloropropyltrimethoxysilane and the amino functional group of octaaminopropyl POSS to generate the adhesion promoter III.
[0015] Preferably, the cellulose is one or a combination of hydroxyethyl cellulose and hydroxyethyl methyl cellulose;
[0016] Preferably, the antifreeze agent is one or a combination of propylene glycol, ethylene glycol, polyethylene glycol, and polypropylene glycol;
[0017] Preferably, the film-forming aid is alcohol ester dodecahydrate;
[0018] Preferably, the pH regulator is one or a combination of 2-amino-2-methyl-1-propanol and N,N-dimethylethanolamine;
[0019] Preferably, the dispersant is an ammonium polyacrylate dispersant;
[0020] Preferably, the defoamer is a silicone defoamer;
[0021] Preferably, the wetting agent is octylphenol polyoxyethylene ether;
[0022] Preferably, the filler is one or a combination of kaolin, quartz sand, talcum powder, and calcium carbonate;
[0023] Preferably, the protective glue is one or a combination of magnesium aluminum silicate and lithium magnesium silicate;
[0024] Preferably, the protective colloid auxiliary agent is one or a combination of bentonite and xanthan gum;
[0025] Preferably, the thickener is polyacrylate;
[0026] Preferably, the preservative is one or a combination of 5-chloro-2-methyl-4-isothiazoline-3-one and 2-methyl-4-isothiazoline-3-one;
[0027] Preferably, the cross-linking agent is one or a combination of polycarbodiimide and N,N-methylenebisacrylamide.
[0028] A crack-resistant base surface renovation composite primer comprises the following raw materials in parts by weight:
[0029] 15-20 parts of water, 5-15 parts of silicone modified polyester resin emulsion, 5-15 parts of silicone acrylic emulsion, 5-15 parts of elastic emulsion, 3-6 parts of hydroxyethyl cellulose, 2-4 parts of hydroxyethyl methyl cellulose, 0.1-1 parts of propylene glycol, 0.5-2 parts of alcohol ester dodecahydrate, 0.1-1 parts of 2-amino-2-methyl-1-propanol, 1-3 parts of polyacrylate ammonium salt dispersant, 1-3 parts of silicone defoamer, 0.1-1 parts of octylphenol polyoxyethylene ether, 5-12 parts of calcium carbonate, 10-18 parts of quartz sand, 1-5 parts of magnesium aluminum silicate, 1-3 parts of bentonite, 1-3 parts of polyacrylate, 1-3 parts of 2-methyl-4-isothiazoline-3-one, 1-3 parts of adhesion promoter, 1-3 parts of N,N-methylenebisacrylamide.
[0030] Beneficial effects:
[0031] The present invention firstly synthesizes three adhesion promoters containing methoxy functional groups based on the molecular design mechanism; then, silicone-modified polyester resin emulsion, silicone-acrylic emulsion and elastic emulsion are used as film-forming resin emulsions, and the adhesion promoter containing methoxy functional groups is added to prepare a base surface renovation composite primer with anti-cracking;
[0032] The experimental results show that the base surface renovation composite primer prepared by the present invention has excellent anti-cracking performance and can meet the technical standard of R-type flexible building exterior wall putty in JG / T 157-2009 "Building Exterior Wall Putty". DETAILED DESCRIPTION
[0033] Embodiment 1:
[0034] Preparation of adhesion promoter I: The alkenyl functional group of allyltrimethoxysilane and the Si-H functional group of 1-n-butyl-1,1,3,3-tetramethyldisiloxane undergo an addition reaction to generate adhesion promoter I, whose chemical structure is:
[0035]
[0036] The specific experimental steps for preparing adhesion promoter I are as follows: under the protection of nitrogen, 1.9 g of 1-n-butyl-1,1,3,3-tetramethyldisiloxane and 20 mL of anhydrous tetrahydrofuran are added to a three-necked flask, stirred at room temperature until completely dissolved, and then 10 mL of anhydrous tetrahydrofuran solution containing 1.6 g of allyltrimethoxysilane and 5 drops of Custer catalyst are sequentially added to the three-necked flask, the temperature is raised to 70°C, stirred and refluxed for reaction for 10 h, cooled to room temperature, the solvent is removed by rotary evaporation, and vacuum dried to obtain adhesion promoter I;
[0037] The nuclear magnetic resonance hydrogen spectrum of adhesion promoter I is characterized as follows: 1H NMR (CDCl3, 400MHz) δ: 0.08 (s, 6H), 0.13 (s, 6H), 0.57-0.61 (t, 2H), 0.68-0.74 (m, 4H), 0.93-0.97 (t, 3H), 1.18-1.29 (m, 4H), 1.41-1.48 (m, 2H), 3.57 (s, 9H).
[0038] Embodiment 2:
[0039] Preparation of adhesion promoter II: Under the catalytic action of a phase transfer catalyst, the hydroxyl functional group of 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane and the chlorine functional group of 3-chloropropyltrimethoxysilane undergo a nucleophilic substitution reaction to generate adhesion promoter II, whose chemical structure is
[0040]
[0041] The phase transfer catalyst is one of benzyltriethylammonium chloride, tetrabutylammonium hydrogen sulfate and tetrabutylammonium bromide; in this experimental example, tetrabutylammonium bromide is selected;
[0042] The specific experimental steps for preparing adhesion promoter II are as follows: 2.5 g of 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane, 2 mL of 30 wt% sodium hydroxide aqueous solution and 50 mL of N,N-dimethylformamide are added to a three-necked flask, stirred at room temperature until all dissolved, then 1.9 mL of 3-chloropropyltrimethoxysilane and 2 mL of a deionized water solution containing 1.1 g of tetrabutylammonium bromide are added dropwise to the three-necked flask in sequence, the temperature is raised to 70° C., stirred for reaction for 10 h, cooled to room temperature, the solvent is removed by rotary evaporation, and vacuum dried to obtain adhesion promoter II;
[0043] The nuclear magnetic resonance hydrogen spectrum of adhesion promoter II is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.06 (s, 6H), 0.11 (s, 6H), 0.59-0.63 (t, 4H), 0.74-0.77 (t, 4H), 1 .51-1.58(m, 4H), 1.69-1.76(m, 4H), 3.25-3.29(t, 4H), 3.39-3.43(t, 4H), 3.57(s, 18H).
[0044] Embodiment 3:
[0045] Preparation of adhesion promoter III: Adhesion promoter III is generated by a nucleophilic substitution reaction between the bromine functional group of 3-chloropropyltrimethoxysilane and the amino functional group of octaaminopropyl POSS (OA-POSS), and its chemical structure is:
[0046]
[0047] The specific experimental steps for preparing adhesion promoter III are as follows: 4.4 g of octaaminopropyl POSS, 1.5 g of sodium bicarbonate and 50 mL of N,N-dimethylformamide are added to a three-necked flask, dissolved at room temperature for 1 h under nitrogen protection and mechanical stirring, then 4.2 mL of 3-chloropropyltrimethoxysilane is added dropwise to the three-necked flask, the temperature is raised to 60 ° C, stirred for 12 h, cooled to room temperature, the solvent is removed by rotary evaporation, and vacuum dried to obtain adhesion promoter III;
[0048] The nuclear magnetic resonance hydrogen spectrum of adhesion promoter III is characterized as follows: 1 H NMR (CDCl3, 400MHz) δ: 0.56-0.70 (m, 32H), 1.46-1.62 (m, 32H), 2.60-2.74 (m, 32H), 3.57 (s, 72H).
[0049] Embodiment 4:
[0050] The method for preparing a crack-resistant base surface renovation composite primer comprises the following steps:
[0051] Step 1, preparing a pre-solution: according to the formula in Table 1, water, silicone-modified polyester resin emulsion, silicone-acrylic emulsion, elastic emulsion, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, propylene glycol, alcohol ester dodecahydrate, 2-amino-2-methyl-1-propanol, polyacrylate ammonium salt dispersant, silicone defoamer and octylphenol polyoxyethylene ether are added into a disperser and mixed, and stirred at 800 r / min for 60 min to prepare a pre-solution;
[0052] Step 2, preparing a crack-resistant base surface renovation composite primer: according to the formula in Table 1, calcium carbonate, quartz sand, magnesium aluminum silicate, bentonite, polyacrylate, 2-methyl-4-isothiazoline-3-one and adhesion promoter are added to the pre-solution prepared in step 1, stirred at 1000 r / min for 60 min, then N,N-methylenebisacrylamide is added, and stirring is continued at 1000 r / min for 60 min to prepare a crack-resistant base surface renovation composite primer;
[0053] Table 1 Raw material formula of anti-cracking base surface renovation composite primer
[0054]
[0055]
[0056] Among them, when the adhesion promoters are adhesion promoter I, adhesion promoter II, and adhesion promoter, respectively, the anti-cracking base surface renovation composite primer I, the anti-cracking base surface renovation composite primer II, and the anti-cracking base surface renovation composite primer III are prepared in sequence.
[0057] Comparative Example 1:
[0058] Preparation of composite primer a: Compared with the anti-cracking base surface renovation composite primer I, the only difference is that silicone acrylic emulsion is used to replace the elastic emulsion.
[0059] Comparative Example 2:
[0060] Preparation of composite primer b: Compared with the anti-cracking base surface renovation composite primer I, the only difference is that silicone acrylic emulsion is used to replace the elastic emulsion, and adhesion promoter I is not used.
[0061] Performance Test:
[0062] The anti-cracking base surface renovation composite primer was applied by scraping, and the anti-cracking composite coating was formed after room temperature curing. The performance test was carried out, and the results are shown in Table 2.
[0063] Table 2 Performance test results of anti-cracking base surface renovation composite primer
[0064]
[0065] By comprehensively analyzing the above experimental results, the following conclusions can be drawn:
[0066] Conclusion 1: The composite primer for base surface renovation prepared by adding elastic emulsion to the formula has excellent anti-cracking performance and can meet the technical standards of R-type flexible building exterior wall putty in JG / T 157-2009 "Building Exterior Wall Putty" (the maximum width of the base crack before the putty layer cracks> 0.3mm, the bonding strength> 0.6MPa);
[0067] Conclusion 2: Compared with the composite primer without adding adhesion promoter, the composite primer for base surface renovation prepared by using the newly developed adhesion promoter in the present invention has achieved a beneficial technical effect of significantly improving the bonding strength performance;
[0068] Among them, adhesion promoter III has the best effect on improving the bonding strength performance of the base surface renovation composite primer;
[0069] The mechanism for producing the above experimental results may be that the silanol functional groups generated by the hydrolysis reaction of the siloxy groups in the adhesion promoter can undergo condensation reaction with the hydroxyl functional groups on the surface of the substrate to form a stable siloxy bond structure, thereby enhancing the adhesion between the coating and the substrate and ensuring that the coating forms a firm adhesion on the surface of the substrate.
Claims
1. A preparation process for a crack-resistant base surface renovation composite primer, characterized in that: The following steps are involved: Step 1: preparing an adhesion promoter containing a methoxy functional group, wherein the adhesion promoter containing a methoxy functional group is one of adhesion promoter I, adhesion promoter II, and adhesion promoter III; The chemical formula of adhesion promoter I is: The chemical formula of adhesion promoter II is: The chemical structure of adhesion promoter III is: Step 2: preparing a crack-resistant base surface renovation composite primer, the formula of the crack-resistant base surface renovation composite primer is: 15-20 parts by weight of water, 5-15 parts by weight of silicone-modified polyester resin emulsion, 5-15 parts by weight of silicone-acrylic emulsion, 5-15 parts by weight of elastic emulsion, 5-10 parts by weight of cellulose, 0.1-1 parts by weight of antifreeze agent, 0.5-2 parts by weight of film-forming aid, 0.1-1 parts by weight of pH adjuster, 1-3 parts by weight of dispersant, 1-3 parts by weight of defoamer, 0.1-1 parts by weight of wetting agent, 15-30 parts by weight of filler, 1-5 parts by weight of protective glue, 1-3 parts by weight of protective glue auxiliary, 1-3 parts by weight of thickener, 1-3 parts by weight of preservative, 1-3 parts by weight of adhesion promoter and 1-3 parts by weight of cross-linking agent.
2. The preparation process of a crack-resistant base surface renovation composite primer according to claim 1, characterized in that: The preparation method of the adhesion promoter I is as follows: the alkenyl functional group of allyltrimethoxysilane and the Si-H functional group of 1-n-butyl-1,1,3,3-tetramethyldisiloxane undergo an addition reaction to generate the adhesion promoter I.
3. The preparation process of a crack-resistant base surface renovation composite primer according to claim 1, characterized in that: The preparation method of the adhesion promoter II is as follows: under the catalytic action of a phase transfer catalyst, the hydroxyl functional group of 1,3-bis(3-hydroxypropyl)-1,1,3,3-tetramethyldisiloxane and the chlorine functional group of 3-chloropropyltrimethoxysilane undergo a nucleophilic substitution reaction to generate the adhesion promoter II.
4. The process for preparing a crack-resistant base surface renovation composite primer according to claim 3, characterized in that: The phase transfer catalyst is one of benzyltriethylammonium chloride, tetrabutylammonium hydrogen sulfate and tetrabutylammonium bromide.
5. The preparation process of a crack-resistant base surface renovation composite primer according to claim 1, characterized in that: The preparation method of the adhesion promoter III is as follows: a nucleophilic substitution reaction occurs between the bromine functional group of 3-chloropropyltrimethoxysilane and the amino functional group of octaaminopropyl POSS to generate the adhesion promoter III.
6. A process for preparing a crack-resistant base surface renovation composite primer according to any one of claims 1 to 5, characterized in that: The cellulose is one or a combination of hydroxyethyl cellulose and hydroxyethyl methyl cellulose; The antifreeze agent is one or a combination of propylene glycol, ethylene glycol, polyethylene glycol, and polypropylene glycol; The film-forming aid is alcohol ester dodecahydrate; The pH regulator is one or a combination of 2-amino-2-methyl-1-propanol and N,N-dimethylethanolamine; The dispersant is an ammonium polyacrylate dispersant; The defoamer is an organosilicon defoamer; The wetting agent is octylphenol polyoxyethylene ether; The filler is one or a combination of kaolin, quartz sand, talcum powder, and calcium carbonate; The protective glue is one or a combination of magnesium aluminum silicate and magnesium lithium silicate; The protective glue auxiliary agent is one or a combination of bentonite and xanthan gum; The thickener is polyacrylate; The preservative is one or a combination of 5-chloro-2-methyl-4-isothiazoline-3-one and 2-methyl-4-isothiazoline-3-one; The cross-linking agent is one or a combination of polycarbodiimide and N,N-methylenebisacrylamide.
7. A crack-resistant base surface renovation composite primer prepared by the process according to any one of claims 1 to 5, characterized in that: The anti-cracking base surface renovation composite primer comprises the following raw materials in parts by weight: 15-20 parts of water, 5-15 parts of silicone modified polyester resin emulsion, 5-15 parts of silicone acrylic emulsion, 5-15 parts of elastic emulsion, 3-6 parts of hydroxyethyl cellulose, 2-4 parts of hydroxyethyl methyl cellulose, 0.1-1 parts of propylene glycol, 0.5-2 parts of alcohol ester dodecahydrate, 0.1-1 parts of 2-amino-2-methyl-1-propanol, 1-3 parts of polyacrylate ammonium salt dispersant, 1-3 parts of silicone defoamer, 0.1-1 parts of octylphenol polyoxyethylene ether, 5-12 parts of calcium carbonate, 10-18 parts of quartz sand, 1-5 parts of magnesium aluminum silicate, 1-3 parts of bentonite, 1-3 parts of polyacrylate, 1-3 parts of 2-methyl-4-isothiazoline-3-one, 1-3 parts of adhesion promoter, 1-3 parts of N,N-methylenebisacrylamide.
Citation Information
Patent Citations
Multifunctional POSS (polyhedral oligomeric silsesquioxane) modified silicon rubber and preparation method thereof
CN103113592A
Anti-cracking putty and using method thereof
CN104403400A
Polyorganosiloxane composition for packaging solar cell module and preparation method of polyorganosiloxane composition
CN112409980A
Flame-retardant modified silane sealant and preparation method thereof
CN116694288A
Curable polyorganosiloxane composition, thermally conductive member, and heat dissipation structure
CN117203284A
Cited By
Stone-like self-leveling paint and preparation process thereof
CN120758126A